The 9-criteria evaluation framework for perceptions survey: the case of VA's Learners' Perceptions Survey. Issue 1 (1st January 2020) - Kashner, T. Michael; Clarke, Christopher T.; Aron, David C.; Byrne, John M.; Cannon, Grant W.; Deemer, David A.; Gilman, Stuart C.; Kaminetzky, Catherine P.; Loo, Lawrence K.; Li, Sophia; Wicker, Annie B.; Keitz, Sheri A.
ABSTRACT: For its clinical, epidemiologic, educational, and health services research, evaluation, administrative, regulatory, and accreditation purposes, the perceptions survey is a data collection tool that asks observers to describe perceptions of their experiences with a defined phenomenon of interest. In practice, these surveys are often subject to criticism for not having been thoroughly evaluated before its first application using a consistent and comprehensive set of criteria for validity and reliability. This paper introduces a 9-criteria framework to assess perceptions surveys that integrates criteria from multiple evaluation sources. The 9-criteria framework was applied to data from the Department of Veterans Affairs' Learners' Perceptions Survey (LPS) that had been administered to national and local samples, and from findings obtained through a literature review involving LPS survey data. We show that the LPS is a robust tool that may serve as a model for design and validation of other perceptions surveys. Findings underscore the importance of using all nine criteria to validate perceptions survey data.